The growth of foot arches and influencing factors - Ferial Hadipoetro Idris (Paediatrica Indonesiana, 2005)
Background Foot arches are important components for body sup-port. Foot arch deformity caused by growth abnormalities causeserious limitations in daily activities.Objectives To determine the patterns of foot arch growth, factorsinfluencing foot arch growth, and the timing for intervention in er-rant growth patterns.Methods A cross-sectional study evaluated the foot arches of chil-dren aged 0-18 years according to age and sex. Subjects includedhad no evidence of physical abnormality other than flat foot, knock-knee, or bow leg. Subjects were grouped per year of age. Data onfoot arch class, age, sex, weight, height, medial intercondylar dis-tance, and medial intermalleolar distance were recorded. Chi-square test, correlation, binary and linear regressions, general lin-ear model, and contrast matrix were performed.Results In 8376 children aged 0-18 years, flat foot grade 3 hadstable proportions in all age groups. Flat foot grade 2 and 1 hadsmaller proportions in older age groups than in younger ones. Theproportions of normal foot was greater in older age groups. Boysat the age of 7 and girls at 9 have a small percentage of pes cavus.The mean foot arch measurements were consistent with flat footgrade 2 at age 0-3 years, flat foot grade 1 at 4 years, and normalfoot at age 18. Median foot arch measurement of children 0-10years old was consistent with flat foot grade 1, while that of chil-dren 11 years old was consistent with normal foot. Age and heightgave positive influence. Based on these measurements we inferthat the optimal time for intervention is 0-7 years for boys and 0-3years for girls.Conclusion The proportion of flat foot grade 3 is stable through-out age groups, that of flat foot grade 2 and 1 are smaller in olderage groups, and that of normal foot is greater in older age groups.Overgrowth happens in very small percentages after age of 7 inboys and 9 in girls. Age, sex, height, weight, and growth of theknees are influencing factors